Monte Carlo simulations and phantom validation of low-dose radiotherapy to the lungs using an interventional radiology C-arm fluoroscope. (February 2022) - Roa, D.; Leon, S.; Paucar, O.; Gonzales, A.; Schwarz, B.; Olguin, E.; Moskvin, V.; Alva-Sanchez, M.; Glassell, M.; Correa, N.; Moyses, H.; Shankar, A.; et al.
Highlights: kV x-rays can deliver an effective low-dose radiotherapy to a COVID-19 patient. Suitable field arrangements result in a homogeneous dose distribution to the lungs. kV x-rays low-dose radiotherapy could be a treatment option until vaccines reach those regions. Low-income countries could benefit from this immediate treatment option. Abstract: Purpose: To use MC simulations and phantom measurements to investigate the dosimetry of a kilovoltage x-ray beam from an IR fluoroscope to deliver low-dose (0.3–1.0 Gy) radiotherapy to the lungs. Materials and Methods: PENELOPE was used to model a 125 kV, 5.94 mm Al HVL x-ray beam produced by a fluoroscope. The model was validated through depth-dose, in-plane/cross-plane profiles and absorbed dose at 2.5-, 5.1-, 10.2- and 15.2-cm depths against the measured beam in an acrylic phantom. CT images of an anthropomorphic phantom thorax/lungs were used to simulate 0.5 Gy dose distributions for PA, AP/PA, 3-field and 4-field treatments. DVHs were generated to assess the dose to the lungs and nearby organs. Gafchromic film was used to measure doses in the phantom exposed to PA and 4-field treatments, and compared to the MC simulations. Results: Depth-dose and profile results were within 3.2% and 7.8% of the MC data uncertainty, respectively, while dose gamma analysis ranged from 0.7 to 1.0. Mean dose to the lungs were 1.1-, 0.8-, 0.9-, and 0.8- Gy for the PA, AP/PA, 3-field, and 4-field after isodose normalization to cover ∼ 95% of each lung volume. Skin dose toxicity was highest for the PA and lowest for the 4-field, and both arrangements successfully delivered the treatment on the phantom. However, the dose distribution for the PA was highly non-uniform and produced skin doses up to 4 Gy. The dose distribution for the 4-field produced a uniform 0.6 Gy dose throughout the lungs, with a maximum dose of 0.73 Gy. The average percent difference between experimental and Monte Carlo values were −0.1% (range −3% to +4%) for the PA treatment and 0.3% (range −10.3% to +15.2%) for the 4-field treatment. Conclusion: A 125 kV x-ray beam from an IR fluoroscope delivered through two or more fields can deliver an effective low-dose radiotherapy treatment to the lungs. The 4-field arrangement not only provides an effective treatment, but also significant dose sparing to healthy organs, including skin, compared to the PA treatment. Use of fluoroscopy appears to be a viable alternative to megavoltage radiation therapy equipment for delivering low-dose radiotherapy to the lungs.